Plasmonic resonance excited dual Z-scheme BiVO4/Ag/Cu2O nanocomposite: synthesis and mechanism for enhanced photocatalytic performance in recalcitrant antibiotic degradation. Issue 7 (24th May 2017) - Deng, Yaocheng; Tang, Lin; Zeng, Guangming; Feng, Chengyang; Dong, Haoran; Wang, Jiajia; Feng, Haopeng; Liu, Yani; Zhou, Yaoyu; Pang, Ya
Abstract : Novel dual Z-scheme BiVO4 /Ag/Cu2 O nanocomposite was prepared and presented enhanced photocatalytic activity. Abstract : The utilization of solar energy based on semiconductor photocatalysts for pollutant removal and environmental remediation has become a research hot spot and attracted great attention. In this study, a novel ternary BiVO4 /Ag/Cu2 O nanocomposite has been successfully synthesized via simple wet impregnation of Cu2 O particles coupled with a subsequent photo-reduction pathway for the deposition of metallic Ag on the surface of BiVO4 . The resulting BiVO4 /Ag/Cu2 O photocatalyst was used for the degradation of tetracycline (TC) under visible light irradiation ( λ > 420 nm). Results showed that the coating contents of the Cu2 O and Ag particles presented a great effect on the eventual photocatalytic activity of the photocatalysts, and the optimum coating contents of Cu2 O and Ag were obtained with their mass ratios of 3% and 2%, respectively. Under optimum conditions, nearly 91.22% TC removal efficiency was obtained based on ternary BiVO4 /Ag/Cu2 O nanocomposites, higher than that of pure BiVO4 (42.9%) and binary BiVO4 /Cu2 O (65.17%) and BiVO4 /Ag (72.63%) nanocomposites. Meanwhile, the enhanced total organic carbon (TOC) removal efficiency also indicated the excellent photocatalytic degradation ability of the BiVO4 /Ag/Cu2 O nanocomposites. As for their practical application, the effects of initial TC concentration, various supporting electrolytes and different irradiation conditions were investigated in detail. Three-dimensional excitation–emission matrix fluorescence spectroscopy (3D EEMs) was used to show the by-products of TC molecule degradation. Cycling experiments indicated the high stability of the as-prepared photocatalysts. Furthermore, the results obtained from radical trapping experiments and ESR measurements suggested that the photocatalytic degradation of TC in the BiVO4 /Ag/Cu2 O based photocatalytic system was the joint action of the photogenerated holes (h + ), superoxide radical (˙O2 − ) and hydroxyl radical (˙OH). The enhanced photocatalytic activity of BiVO4 /Ag/Cu2 O was attributed to the synergistic effect of Cu2 O, Ag and BiVO4, especially the surface plasmon resonance effect and the established local electric field brought about by metallic Ag. Additionally, to deeply understand the reaction mechanism, a dual Z-scheme charge transfer pathway has been proposed.